Importance of Arginine as Immune Regulator in Animal Nutrition - Birmani, Muhammad Waseem; Raza, Aqeela; Nawab, Aamir; Tang, Shuyan; Ghani, Muhammad Waseem; Li, Guanghui; Xiao, Mei; An, Lilong (International Journal of Veterinary Sciences Research, 2019)
Arginine grouped in a gluconeogenic amino acid extensively found in the animal's cells. Fast growing animals require more arginine in their diet as broilers and pigs. It plays a critical role in ammonia detoxification and protein biosynthesis. Arginine is not only involved in the synthesis and catabolism of a variety of nutrients in the animal body but mainly act as an immunomodulatory mediator. Along with nutritional function has immune-related functions. In urea cycle act as an important intermediate and also catalyzes the production of ornithine by enzyme arginase and converted into polyamines that involved later in cell proliferation and wound healing. Nitric oxide synthases catalyze the production of nitric oxide from arginine and NO is a cellular signaling molecule for immune regulation. Many hormones secretion increased by arginine particularly the growth hormones which could enhance the immune function. Arginine metabolism pathway and its downstream metabolites like nitric oxide and polyamines might be vital for the activation of T-cell and ultimately take part in adaptive immunity. For immune regulation, arginine could stimulate the production of different immune cytokines. In this paper, in the perspective to provide significance reference about arginine in the immune study, the arginine immune mechanism and use of arginine in animals will review.